Pembuatan Website Company Profile Sebagai Media Promosi Menggunakan Wordpress Pada CV. Duta Perkasa Pasuruan - Audy Aprilia; Maskur (PT. Hasba Edukasi Mandiri, 2025)
This research aims to determine the creation of a company profile website used WordPress in the CV. Duta Perkasa Pasuruan and know how to measure effectiveness on its company profile website with Webqual method. The type of research used in this research was Action Research. This research used the method of distributing questionnaires to 15 respondents, observation, documentation and interviews. This research measured the effectiveness of newly created websites using the Webqual method. The results of this research showed that: (1) the website that had been created was easy for visitors to use in the usability dimension (2) the website that had been created had present accurate, up-to-date and easy to understand information in the information quality dimension (3) the website that had been created could make it easier users interact on the website on the interaction quality dimension.